An investigation into the effectiveness of using headphones with integrated microphones to simulate concert hall acoustics for musicians in small acoustic environments - Ter Huurne, Tim Hendrik (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.